CHILDREN'S CRIMINAL RESPONSIBILITIES: COMPARATIVE STUDY IN ISLAMIC AND CRIMINAL LAW - Hendrawati, Heni; Nurwati, Nurwati; Budiharto, Budiharto (Varia Justicia, 2018)
The study of criminal liability against child offenders based on Law No. 11 of 2012 concerning the Criminal Justice System of Children and according to Islamic Criminal Law is a very interesting phenomenon to study, especially during this time many phenomena of a minor underage sitting in the accused and detained like a big villain just because of a trivial matter. This study includes the type of research library research, so in this study, researchers conducted data collection through the study and library research on books relating to the problems the authors studied. In analyzing this study, the authors used a comparative method that is comparing child criminal liability in positive criminal law based on Law No. 11 of 2012 concerning the Child Criminal Justice System, with child criminal liability in Islamic criminal law. In Islamic law, a child will not be subject to a punishment for the crime he committed, because there is no legal responsibility for a child of any age until he reaches the age of baliq, qadhi will only have the right to reprimand him or set some restrictions for him to help improve the child in the future. It is expected that this research can contribute to the renewal of national criminal law, especially regarding criminal liability committed by children, taking into account the concepts in Islamic criminal law.